The bigger picture: the hidden consequences of the sugar reduction strategy for tackling childhood obesity in the UK - Anabtawi, Ola (2020)
The focus on reducing rates of childhood obesity has become one of the main public health priorities in the United Kingdom. The government is addressing this through various strategies including Public Health England’s sugar reduction programme, which aims to decrease free sugar intake to 5% of individuals’ total energy intake (PHE, 2015a). There is precedent in the UK of using a single-nutrient approach in the management of non-communicable diseases (NCDs), with salt being used to address hypertension, and dietary fat for cardiovascular diseases and obesity. Using a four mixed- method studies, this PhD aims to investigate possible unintended consequences associated with the one-nutrient focus on sugar, including demonising the single nutrient targeted, promoting unhealthy dieting, detracting from a balanced healthy diet, creating stigma around obesity and exacerbating other health-related inequalities.